EQUITY AND ACCESS : EXAMINING OPPORTUNITIES OF ADVANCED PLACEMENT FOR AFRICAN AMERICAN STUDENTS - Campbell, Elaine A. (East Carolina University, 2014)
This research study used Invitational Education Theory to examine the attitudes and perceptions educators have concerning college-level coursework and the potential impact these attitudes and perceptions had on the enrollment of African American students in AP coursework. The data acquired was obtained from educators in two high schools located in the southeastern part of the United States using the Equal Opportunity Schools Staff Survey. Findings from this research are discussed in relation to the definition, function, and characteristics of an inviting school environment. Uncovered attitudes and perceptions were analyzed and then categorized according to the four defined functioning levels of Invitational Education Theory. This assessment helped to determine the learning environment created and maintained for students and provide information targeting the school environment possibly impacting African American students' participating in AP coursework. This study seeks to contribute to the existing research regarding the disparities in enrollment existing between African American students and their White peers in Advanced Placement® coursework offerings in the high school setting.
Equity and access : examining opportunities of advanced placement® for African American students
Keywords: Educational leadership; High school teachers--North Carolina--Attitudes; African American high school students--North Carolina; Advanced placement programs (Education)